Determinants of capital structure: Evidence from Chinese listed IT companies - HE, YAO (2018)
This paper investigates capital structure determinants of 305 Chinese listed firms operating in information technology industry over the period from 2012 to 2016. The findings reflect unique institutional and industry feature. Some of capital structure theories and related factors derived from developed countries and other developing economies can also be applied into Chinese companies, especially firm specific characteristics. Firm size and profitability are core robust determinants when considering different measure of leverage. However, due to immature corporate governance structure, board characteristics show different influence with previous studies. State ownership also exerts opposite effect on leverage. Influence of growth opportunities demonstrate unique industry feature, which is high development of IT industry. Furthermore, small firms are found to be more sensitive to these determinants. Also, Chinese firms prefer equity financing and short-term debt which is different from other countries.